The development of environment-based picture storybooks to increase the fourth grade students’ reading interest - Alpiyah Alpiyah; Alben Ambarita; Pargito Pargito (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to produce an environment-based picture storybook to increase the reading interest of fourth-grade elementary school students and obtain the results of book product testing until the suitable book used as reading learning for elementary school students is obtained. This research is development research which consists of three stages, which include (1) Preliminary Study, (2) Product Development, (3) Product Test. The subjects of this study were fourth-grade students of SDN 1 Rajabasa Raya, Rajabasa Sub District, Bandar Lampung City, Lampung Province. The data analysis technique in this study adopted a qualitative descriptive technique. Data collection was carried out using questionnaires and interviews. The product validity was tested by learning material and learning media experts. Based on the research conducted, it was found that: (1) environmental-based picture storybooks can increase students' reading interest; (2) environmental-based picture storybooks are suitable to be used as learning resources in learning to read for elementary school students. The results of this study found that the level of validity of the development of picture storybook learning media products in increasing reading interest in fourth-grade elementary school students was very good.